ANTI-FUNGAL ACTIVITY OF ACALYPHA WILKESIANA: A PRELIMINARY STUDY OF FUNGAL ISOLATES OF CLINICAL SIGNIFICANCE - KATIBI , Oludolapo Sherifat; ABOH , Mercy Itohan; SALAWU , Oluwakayinsola Adeola; KOLA-MUSTAPHA , Adeola; OLATUNJI , Lawrence Aderemi (African Journal of Infectious Diseases (AJID), 2022)
Background: Acalypha wilkesiana (AW), a popular medicinal plant has been used in traditional medicine to treat a variety of skin disorders including pityriasis versicolor and seborrheic dermatitis. As a prelude to clinical trials in humans, an experimental study was carried out to determine the spectrum of antifungal activity of 2 variants of the Acalypha wilkesiana plant. Materials and Methods: The ethanol extract and herbal cream formulation of the dried leaves of 2 cultivars (Macrophylla & Hoffmani) of Acalypha wilkesiana were investigated for in-vitro antifungal activity by disc diffusion and micro-broth dilution techniques. Organisms tested were typed cultures of Malassezia furfur, Candida albicans and Trichophyton rubrum; and clinical strains of Microsporum canis and Epidermophyton floccosum. Results: Both cultivars (Macrophylla and Hoffmanii) of the plant showed good activity against all the fungi tested except Microsporum canis (8.0±0.00; 7.00±0.00 mm). The greatest activity was observed against Trichophyton rubrum (22.0±0.00; 24.00±0.00 mm). The Minimum Inhibitory Concentration (MIC) of the crude extract ranged between 0.25 and 8 mg/ml for all organisms, while that of the herbal cream was 0.31-8mg/ml. The lowest MIC was seen with Candida albicans for both varieties of the plant. The Acalypha wilkesiana Hoffmanii demonstrated a greater activity against Candida albicans and Malassezia furufur than the A. wilkesiana Macrophylla. Conclusion: This study reveals Acalypha wilkesiana leaf extract has potential for development as a cream that can be used to treat superficial fungal skin infections.